2022
DOI: 10.1108/jwl-08-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

Organisational development programmes and employees’ career development: the moderating role of gender

Abstract: Purpose This study aims to investigate the relationship between different organisational development programmes (360-degree feedback; Coaching; Job assignment; Employee assistance programmes; On-the-job training; Web-based career information; Continuous professional development; External education provision) and employees’ career development. The implications of the moderating effects of gender on the relationships between these eight organisational programmes and career development are assessed. Design/meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 145 publications
(171 reference statements)
1
23
1
2
Order By: Relevance
“…3. Job assignment is defined in this study as 'a task identified by the management and given to the employee to perform within a determined time frame to achieve specific work and learning objectives' (Pinnington et al, 2022). The aim of this is to develop skills and experience, improve productivity and performance and increase confidence.…”
Section: Organizational Development Programs and Career Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…3. Job assignment is defined in this study as 'a task identified by the management and given to the employee to perform within a determined time frame to achieve specific work and learning objectives' (Pinnington et al, 2022). The aim of this is to develop skills and experience, improve productivity and performance and increase confidence.…”
Section: Organizational Development Programs and Career Developmentmentioning
confidence: 99%
“…This can contribute to career development through the identification of strengths and areas which need to be worked on. Coaching involves one-to-one learning in a collaborative and reflective relationship. The focus is on achieving the goals which are important for the coachee and it has been shown to have a positive effect on performance outcomes, workplace well-being, resilience and learning. Job assignment is defined in this study as ‘a task identified by the management and given to the employee to perform within a determined time frame to achieve specific work and learning objectives’ (Pinnington et al , 2022). The aim of this is to develop skills and experience, improve productivity and performance and increase confidence. Employee assistance programs (EAPs) are put in place to support workers when dealing with professional and personal challenges.…”
Section: Organizational Development Programs and Career Developmentmentioning
confidence: 99%
See 3 more Smart Citations